Budaya Makan pada Balita Stunting di Desa Rahia Kecamatan Gu Kabupaten Buton Tengah - Rostiani Rostiani; Wa Ode Winesty Sofyani; Hidayah Rahman (JURNAL KABANTI: Kerabat Antropologi, 2024)
Stunted toddlers are often not aware of it, and after two years it will be seen that the toddler is short. Chronic nutritional problems in toddlers are caused by insufficient dietary intake for quite a long time because parents or families do not know or are not aware of providing food according to their children’s nutritional needs. Based on data on the prevalence of nutritional status of children under five with indicators of height based on age (height/a) at the Central Buton Health Office. This study aimed to discover the eating culture of stunted toddlers and what causes stunting to occur in Rahia Village, Gu District, Central Buton Regency. This study uses ethnographic methods with observation participation and in-depth interviews. The results of this study indicate that the eating culture of stunting toddlers in Rahia Village, Gu District, Central Buton Regency is influenced by a lack of parental knowledge so that stunting is still difficult to overcome. The causes of stunting include the provision of MP-ASI too early, the quality of food is less nutritious, dietary restrictions for pregnant women, babies who do not receive immunizations, irregular meal schedules, low mother’s knowledge and lack of socialization regarding stunting education.